2488. The Impact of Reactogenicity After Administration of the Recombinant Zoster Vaccine Upon the Physical Functioning and Quality of Life of Older Adults. (26th November 2018) - Schmader, Kenneth E; Levin, Myron J; Grupping, Katrijn; Matthews, Sean; Butuk, David; Chen, Michael; El Idrissi, Mohamed; Fissette, Laurence A; Fogarty, Charles; Hartley, Paul; Klein, Nicola P; Nevarez, Max; et al.
Abstract: Background: Herpes zoster (HZ) and its related complications are associated with a significant burden of illness in older adults, which negatively impacts patients' physical functioning and quality-of-life (QoL). The recombinant zoster vaccine (RZV) shows high efficacy for the prevention of HZ in older adults but is associated with local and systemic reactions. Therefore, this study assessed the impact of RZV reactogenicity upon the physical functioning and QoL of participants. Methods: 401 adults aged ≥50 years received a dose of RZV at 0 and 2 months in this open-label, single-arm, multicenter study (NCT02979639). Changes in mean SF-36 Physical Functioning score were assessed between pre-dose-1 vaccination and post-dose-1 vaccination for 7 days (primary endpoint). Decreased scores are associated with decreased physical functioning. QoL, reactogenicity and safety were also assessed. The current analysis was performed post-dose-1 vaccination of the 2-dose RZV schedule. Results: No clinically meaningful reductions in overall mean SF-36 Physical Functioning scores from pre- to post-RZV dose-1 were observed (mean +1.9 points) and no overall quality-adjusted-life-year loss was recorded post-dose-1. However, grade 3 reactogenicity occurred in 9.5% of participants, and was associated with a transient, clinically-important decrease in SF-36 Physical Functioning score (impacting activities such as walking, carrying groceries, climbing stairs) on Days 1–2 post-first-vaccination (Table 1). The solicited local symptoms were pain (77.5%), redness (23.0%) and swelling (13.3%); the most frequent solicited systemic reactions were fatigue (33.5%), headache (28.3%) and myalgia (26.8%). Conclusion: Overall, the physical functioning and QoL of older adults were not significantly affected by a first RZV dose. Grade 3 reactogenicity was associated with a small transient decrease in physical functioning 1–2 days post-dose-1 that resolved by Day 3 post-vaccination. Funding: GlaxoSmithKline Biologicals SA Disclosures: K. E. Schmader, GSK group of companies: Investigator, Research grant. M. J. Levin, GSK group of companies: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. K. Grupping, GSK group of companies: Employee, Salary. S. Matthews, GSK group of companies: Consultant, Consulting fee. M. El Idrissi, GSK group of companies: Employee and Shareholder, Salary. L. A. Fissette, GSK group of companies: Employee, Salary. C. Fogarty, Medical Research: Investigator, Research grant. N. P. Klein, GSK group of companies: Investigator, Research support. M. Nevarez, GSK group of companies: Investigator, Investigator stipend. K. Uusinarkaus, GSK group of companies: Investigator, Research grant. L. Oostvogels, GSK group of companies: Employee, Salary. D. Curran, GSK group of companies: Employee and Shareholder, GSK shares and Salary.